The dynamics of actin filament polymerization in activated leukocytes under experimental diabetes mellitus against the background of agmatine administration - Brodyak, I.V.; Bila, I.I.; Sybirna, N.O. (Вiopolymers and Cell, 2017)
Aim. To research the impact of agmatine on the redistribution of actin fractions, which are repre-sented by cytoskeletal actin filaments, short actin filaments of the plasma membrane skeleton and actin monomers (G-actin) in rat leukocytes under experimental diabetes mellitus (EDM). Methods. Leukocytes were lyzed in Triton X-100 and subjected to centrifugation to obtain cytoskeletal actin filaments, short actin filaments and actin monomers, which were separated in SDS-PAAG, followed by the immunoblot analysis of anti-actin antibodies. Results. Under EDM, an intensifi-cation of the process of short actin filament depolymerization and an increase in the G-actin con-tent were observed in leukocytes activated by sialospecific wheat germ lectin (WGA). Against a background of agmatine administration, the response dynamics to the WGA-stimulating effect was characterized by an increase in actin polymerization in the fraction of cytoskeletal filaments already after 0.5 min exposure to lectin, an exceptionally rapid depolymerization process after 1 min of the lectin treatment, and return to the initial indices after 3 min exposure to lectin. Conclusions. In leukocytes of animals with EDM against a background of agmatine administration, the transduction of WGA-induced signal through sialoglycoconjugates causes the actin redistribution. It indicates that this polyamine helps to restore and maintain a functional response of leukocytes to the activation signals.